Irrigation water salinity structures the bacterial communities of date palm (Phoenix dactylifera)-associated bulk soil - Loganathachetti, Dinesh Sanka; Alhashmi, Fardous; Chandran, Subha; Mundra, Sunil (Frontiers in Plant Science, 2022)
The irrigation of date palms (Phoenix dactylifera) with saline groundwater is routinely practiced in the agroecosystems of arid environments because of freshwater scarcity. This leads to salts deposition in topsoil layers and increases soil salinization. However, how different irrigation sources affect soil microbiota is poorly understood. Bulk soil samples were collected from date farms receiving non-saline water and saline groundwater to examine bacterial communities using metabarcoding. Overall, bacterial diversity measures (Shannon diversity index, richness, and evenness) did not vary between irrigation sources. Bacterial communities were structured based on irrigation water sources and were significantly associated with their electrical conductivity. Of 5,155 operational taxonomic units (OTUs), 21.3% were unique to soil irrigated with saline groundwater, 31.5% received non-saline water irrigation, and 47.2% were shared. The Proteobacteria abundance was higher in soil under saline groundwater irrigation while Actinobacteriota abundance was lower. A compositional shift at the genera level was also evident; the abundance of Subgroup_10 and Mycobacterium was higher under saline groundwater irrigation. Mycobacterium was a key indicator OTU under saline groundwater irrigation while Solirubrobacter was an indicator of non–saline water irrigation. Functional gene analyses showed enrichment of fatty acid, cell wall, and starch biosynthesis pathways in soil under saline groundwater irrigation. These findings provide insights into how ‘salinity filtering’ influences bacterial communities, key taxa, and the potential metabolic function in soil under increasing irrigation water salinities, and have broad implications for arid agroecosystems.